Indonesian Slang Word Formation Processes in TikTok - Wenas, Ryani Airin Putri; Murniati, Cecilia Titiek; Hartono, Heny (Celt: A Journal of Culture, English Language Teaching & Literature, 2024)
Language changes over time due to social and cultural factors. These changes are evident through language varieties such as standard and non-standard languages, dialects, accents, and registers. This research focuses on one type of language variation, namely slang. Slang words show that language is constantly changing. For example, there are many new slang words that emerge and old ones that are no longer used or replaced. Slang also reflects people’s creativity because through slang we can see how someone can be very creative in making new words or modifying existing words. This research aims to identify the slang words that appear in the comments section of the TikTok during June to December 2022 and analyze the word formation process of each slang found. The authors used the qualitative descriptive method in order to present the data thoroughly. This study found that there were 39 slang words that appeared repeatedly and there were six most common word formation processes found in TikTok comments, namely blending, clipping, borrowing, acronym, affixation, and multiple processes. The most frequent processes are blending and clipping. The least frequent word formation processes are affixation and borrowing.